2020
DOI: 10.1007/s11205-020-02509-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Work-Family Relationship on Perceived Health 5-Years Later: The Moderating Role of Job Insecurity

Abstract: Previous studies on the work-family relationship have analyzed the influence of work-family conflict and work-family enrichment on an individuals’ lives, namely on their well-being and health. Besides, attempts have been made to analyze the influence of other aspects of the labor context on this relationship, such as job insecurity. However, few have analyzed this relationship and interaction from a longitudinal perspective. Thus, the main purpose of this study is to analyze the moderating role of job insecuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 96 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…The existing, yet scant research on the consequences of qualitative job insecurity has reported a decrease in worker well-being (De Witte et al, 2016), commitment (Urbanaviciute et al, 2015), job satisfaction (Urbanaviciute et al, 2015), organizational identification, and justice (Chirumbolo et al, 2017) as well as decreased depressive symptoms (Vander Elst et al, 2014), greater work demands, and conflict in the work–family relationship (Bandeira et al, 2021; Lästad et al, 2014). However, as noted, the consequences of qualitative job insecurity on performance have been less investigated (Jiang and Lavaysse, 2018; Probst et al, 2020; Sverke et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The existing, yet scant research on the consequences of qualitative job insecurity has reported a decrease in worker well-being (De Witte et al, 2016), commitment (Urbanaviciute et al, 2015), job satisfaction (Urbanaviciute et al, 2015), organizational identification, and justice (Chirumbolo et al, 2017) as well as decreased depressive symptoms (Vander Elst et al, 2014), greater work demands, and conflict in the work–family relationship (Bandeira et al, 2021; Lästad et al, 2014). However, as noted, the consequences of qualitative job insecurity on performance have been less investigated (Jiang and Lavaysse, 2018; Probst et al, 2020; Sverke et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the opposite effects for mothers and fathers is more difficult to align with this possible explanation. Previous research found that job security is positively related to work-family enrichment (Bandeira et al, 2021) and emphasizes the importance of including interaction factors with gender (e.g. gender ideology) due to the unclear and inconsistent results on the gender effect on job insecurity (Gaunt and Benjamin, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Safety behavior refers to behavior that will not infringe, endanger, harm, or cause los, and which is affected by personality traits [ 2 ], emotion control [ 3 ], work–life conflicts [ 4 , 5 ], etc. The unsafe behaviors of employees can cause many injury incidents, especially in the construction industry.…”
Section: Literature Reviewmentioning
confidence: 99%